Impact of station number and duration time per station on the reliability of Objective Structured Clinical Examination (OSCE) scores: a systematic review and meta-analysis - Qiyun Peng; Jiani Luo; Chunyan Wang; Lei Chen; Shenglan Tan (BMC Medical Education)
Abstract Background The Objective Structured Clinical Examination (OSCE) is a systematic and structured assessment tool that evaluates candidates’ professional medical skills in a simulated environment through a series of time-limited stations. The aim of this meta-analysis was to determine the optimal station number and duration time per station of OSCE to achieve good reliability. Methods A comprehensive search was conducted across PubMed and Embase from inception until August 2024, without language restrictions. Studies were included if they provided data on the station number and duration time of OSCE, along with Cronbach’s alpha. A random-effects model was used to pool the data. Results A total of 23 studies encompassing 26 Cronbach’s alpha were finally included. Cronbach’s alpha values ranged from 0.43 to 0.93, and 11 studies demonstrated good internal consistency (Cronbach’s alpha ≥ 0.8). The analysis indicated that a design of 5–10 stations, with each station lasting less than 10 min, yielded the best internal consistency (Cronbach’s alpha = 0.88, 95% CI: 0.86, 1.00). Conclusions This meta-analysis suggests that the station number of OSCE falling in between 5 and 10, with each station time lasting no more than 10 min are likely to yield good reliability and strong internal consistency.